Peer conformity in the "manis manja" community - Aulia, Tesi; Yandri, Hengki; Juliawati, Dosi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Peer conformity is a problem that almost everyone experiences; both adults and adolescents often adjust their behavior and opinions to their peer group. Thus, this study analyzed the condition of peer conformity in the waria community "Manis Manja." This study used a descriptive quantitative approach that tried to describe the data as it is. The participants in this study were members of the waria community "Manis Manja" in Kerinci Regency, which amounted to 10 people. The research data were revealed using the Peer Conformity Scale, which has been tested for validity and reliability. The study's results were processed and analyzed using statistical analysis of categorization norms. The results showed that the condition of peer conformity in the "Manis Manja" community in Kerinci Regency was in the medium category, meaning that members of the "Manis Manja" community made adjustments to their group environment by the norms or rules in their group, and tended to follow the styles and behaviors of other group members. Peer conformity influences adolescent behavior through the behavior in a group. This research is the first to describe peer conformity in the transgender community. This research is the first to reveal the condition of peer conformity in the "Manis Manja" waria community, Kerinci Regency. This research discusses the problem of peer conformity in the "Manis Manja" community.